What Duty to Support the Surface Does a Subsurface Owner Owe? - Robert Bosworth (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1928)
THE liability for damages to the surface caused by subsidence is an ever present threat in all underground mining. In ordinary lode mining, this threat rarely materializes into an action, due to the method of mining metalliferous ores, the dip of the veins, and the nature of the ground itself. In the mining of coal, however, this threat is very real. The coal frequently lies close to the surface, in beds underlying large areas of land of which the surface is suitable for agricultural or urban development. Furthermore, the coal is generally mined by the "room and pillar" method and when the pillars of coal are removed, the subjacent support is destroyed. This question of the duty of surface support has now become a very live one in Colorado. What was waste prairie land a few years ago has become valuable agricultural land dotted here and there with growing towns. Frequent references will be made here to Colorado conditions and adjudicated cases, but those conditions and cases and the conclusions to be drawn therefrom are applicable to all coal-mining states. Briefly stated, the question is "Does the owner of the substrata or underlying mineral owe any duty of surface support to the owner of the superjacent strata or surface?" There is -no absolute duty of support owed by the mineral owner and this assertion is made with full knowledge of numerous expressions to the contrary by courts of Pennsylvania, Illinois, Colorado and other coal-mining states. Whether or not any duty exists depends upon the circumstances surrounding each case, and since in the nature of things those circumstances are rarely identical, there can be no absolute rule.